1993
DOI: 10.1007/bf01627702
|View full text |Cite
|
Sign up to set email alerts
|

Arteries to the great and second toes based on three-dimensional analysis of 100 cadaveric feet

Abstract: Three-dimensional arteriography was used to analyse the arterial supply of the great and second toes of 100 cadaveric feet down to the microsurgical level. This information will aid in successful composite tissue transfers of these toes to the hand. The arterial blood supply of the great toe came principally from the first dorsal metatarsal a. (78%) and the first plantar metatarsal a. (22%), and secondarily from the medial tarsal aa. and the three terminal branches of the medial plantar a. For the second toe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A few studies have reported on the arterial anatomy of the second toe. Hameda reported that the first dorsal (in 78% of the feet studied) and plantar metatarsal arteries (22%) supplied blood from the medial side, and the second dorsal (78%) and plantar metatarsal arteries (22%) did so from the lateral side 4. Despite the importance of toenail transfer, the exact location of the branches of the digital artery has not been fully defined.…”
mentioning
confidence: 99%
“…A few studies have reported on the arterial anatomy of the second toe. Hameda reported that the first dorsal (in 78% of the feet studied) and plantar metatarsal arteries (22%) supplied blood from the medial side, and the second dorsal (78%) and plantar metatarsal arteries (22%) did so from the lateral side 4. Despite the importance of toenail transfer, the exact location of the branches of the digital artery has not been fully defined.…”
mentioning
confidence: 99%
“…The vascular anatomy of the second toe and MT2 has been reported previously. [14][15][16] The first dorsal metatarsal artery gives off several musculoperiosteal branches to the MT2 and, although not specifically studied in the present article, it is reasonable to assume that after careful limited periosteal stripping, the two segments of the osteotomized MT2 would retain adequate vascularity. Further research in this regard is warranted.…”
Section: Discussionmentioning
confidence: 79%
“…19 Several other studies have reported dorsal-dominant blood supply to the second toe as high as 78%. 20,21 In our review, 7 of 11 patients (63%) were noted to have a plantar-dominant vascular system, one patient had a nondominant vascular system, and three patients had a dorsal-dominant system. The flap is typically disarticulated at the metatarsophalangeal joint, but it can also be taken distal or proximal to this level.…”
Section: Operative Techniquementioning
confidence: 83%